Organizational Culture in relation to the Teaching Performance of Mariano Melgar Breña College - Lima, 2018 - Alvarez Bastidas, Surena Edith (2019)
The organizational culture, it is important to understand the success or failure of a management, it helps us to know the problem that could occur in an organization, the present study deals with the relationship of the organizational culture with the teaching performance of the Mariano Melgar Educational Institution of Breña, with the objective of analyzing this relationship and knowing its effects. The population was made up of 185 individuals and the sample was 127 among teachers and students. Two questionnaires were used, one on organizational culture, and another questionnaire on teacher performance. The results showed that there is a considerable positive relationship between organizational culture and teaching performance, there is an average level of organizational culture of 75%, and an average teaching performance of 63%, which indicates that if the organizational culture is high, then teacher performance will also be high or viceversa.